VERFREMDUNGSEFFEKT (EFEK ALIENASI) DALAM TEKS DRAMA MUTTER COURAGE UND IHRE KINDER KARYA BERTOLT BRECHT - Isti Hayati (Allemania, 2013)
This research aims to reveal the Epic Theater and Alienation Effects (Verfremdungseffekt) in the text of Drama Mutter Courage und ihre Kinder by Bertolt Brecht. To make an audience think critically of the story presented, Bertolt Brecht’s use of effects called alienation effects (Verfremdungseffekt). In the text of the Drama entitled Mutter Courage und ihre Kinder, Alienation effects appearance in the form of songs, history record, language that was made foreign, an estimate of titles and contents, and contact with the audience, and the two different things go together. Alienation effect was made by Brecht that the reader / viewer can take a distance with the story, which was staged and can think rationally on Mutter Courage stories that live in the age of the war.